Humanism in islam - Boisard, Marcel A. (Islamic Book Trust Kuala Lumpur, Malaysia, 2003)
Humanism in Islam has not been drafted only out of sympathy for the Muslims but also on account of historical evidence: Islamic civilization was the first to outline clear and mandatory provisions for protecting the destiny of man and society, and for creating order in the ties between peoples.